Factors Analysis Related to the Response Time of Nursing Services Based on the ATS II Category in the Emergency Installation - Sumbara, .; Fadli, .; Safruddin, . (KnE Life Sciences, 2021)
The response time for nursing refers to the time required to provide emergency nursing care to patients following the triage assessment. This study seeks to analyze the factors associated with the response time of nursing services based on the ATS II category in the emergency department and the magnitude of the influence of age, knowledge, education, and length of work on response time. The method used in this research was correlational, with a cross sectional method and a questionnaire sheet. The research sample was comprised of 20 nurses. Data analysis was used the Pearson correlation test. The results showed that there was a relationship between age, education, length of work and knowledge with response time, with the value of each variable as follows: age with a p-value of 0.015 and r 0.533; education with a p-value of 0.005 and r 0.601; length of work with a p-value of 0.000 and r 0.739; and knowledge with a p-value of 0.002 and r 0.638. From the results of the analysis, it can be concluded that the strongest determinant factors for response time are length of work and level of knowledge. This study concludes that improving nurse education and training related to handling emergency patients should be prioritised. Keywords: length of work; knowledge; education, response time; age